Analisis Perlindungan Hukum bagi Konsumen Belanja Online - I Putu Agus Putra Arimbawa; I Gede Pasek Eka Wisanjaya (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted with the aim of analyzing the legal protection applied to online shopping consumers. The research can be carried out by using a normative juridical method that is closer to descriptive qualitative. The source of the data obtained in this study is secondary data with data collection techniques, namely literature review. Various sources of literature both from journals, books and laws and regulations are reviewed and analyzed and analyzed. The analysis was carried out descriptively which was then taken to generalize A statement that summarizes the problem in the research. The results of the study show that consumer protection is governed by Law no. 8 of 1999 on Consumer Protection. In online shopping transactions, the ITE Law also applies, namely Law number. 19 of 2016 on Information and Electronic Transactions. In resolving online shopping disputes, it can be done in 3 ways, namely instant claims (negotiation, mediation, etc.), asking for help from the Consumer Dispute Settlement Agency, and through the courts.